Accessing a functional database via CODASYL-DML transactions - Coker, Harry Jr. (1987)
Conventional approaches to the design and implementation of database systems have been based upon the premise of a single data model with its model-based data language, thus restricting the database system to transactions based solely on a specific model and written in a specific data language. This traditional approach has drastically hindered the widespread interactions of database systems basad on various data models and languages. As an alternative to this traditional and less effective approach to database systems, the multi-lingual database system (MLDS) has evolved. MLDS has allowed the user to access and interact with numerous databases in various data models via their corresponding data languages. This thesis implements a methodology for accessing and manipulating databases stored in a particular data model via transactions of a separate data model; specifically, a functional database is access via CODASYL-DML transactions. This interface is the initial move toward extending MLDS to a thoroughly Multi-Model Database System (MMDS). Approved for public release; distribution is unlimited. Lieutenant, United States Navy http://archive.org/details/accessingfunctio1094522588